2021
DOI: 10.1007/s15010-021-01730-6
|View full text |Cite
|
Sign up to set email alerts
|

Baricitinib combination therapy: a narrative review of repurposed Janus kinase inhibitor against severe SARS-CoV-2 infection

Abstract: Purpose The Coronavirus disease 2019 (COVID-19) pandemic is one of the most devastating global problems. Regarding the lack of disease-specific treatments, repurposing drug therapy is currently considered a promising therapeutic approach in pandemic situations. Recently, the combination therapy of Janus kinase (JAK) inhibitor baricitinib has been authorized for emergency COVID-19 hospitalized patients; however, this strategy's safety, drug-drug interactions, and cellular signaling pathways remain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 88 publications
0
18
0
Order By: Relevance
“…With respect to viral dynamics, no significant differences in time to low viral load or positive IgG antibody were identified between treatment groups, which might be attributed to their comparable initial viral load, and antibody response was not impaired by either drug ( Bronte et al, 2020 ; Masiá et al, 2020 ). While tocilizumab use was associated with a shorter time to viral clearance of marginal significance, further studies directly comparing tocilizumab and baricitinib in COVID-19 patients are needed to delineate their effects on SARS-CoV-2 RNA shedding, as the current literature is limited with inconclusive evidence on the association between the use of these immunomodulatory drugs and viral clearance, which is further complicated by the diverse clinical characteristics of COVID-19 patients (including but not limited to their age, albumin level, initial viral load, disease severity, and immunocompetence) ( Masiá et al, 2020 ; Akbarzadeh-Khiavi et al, 2021 ; Cogliati Dezza et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to viral dynamics, no significant differences in time to low viral load or positive IgG antibody were identified between treatment groups, which might be attributed to their comparable initial viral load, and antibody response was not impaired by either drug ( Bronte et al, 2020 ; Masiá et al, 2020 ). While tocilizumab use was associated with a shorter time to viral clearance of marginal significance, further studies directly comparing tocilizumab and baricitinib in COVID-19 patients are needed to delineate their effects on SARS-CoV-2 RNA shedding, as the current literature is limited with inconclusive evidence on the association between the use of these immunomodulatory drugs and viral clearance, which is further complicated by the diverse clinical characteristics of COVID-19 patients (including but not limited to their age, albumin level, initial viral load, disease severity, and immunocompetence) ( Masiá et al, 2020 ; Akbarzadeh-Khiavi et al, 2021 ; Cogliati Dezza et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…2 ) could be considered an impediment to treating a viral infection (e.g. COVID-19), with IFNs preventing virus replication during the early stage of an infection, such an action may alleviate the hyper-inflammation (resulting from excessive cytokine production) seen with severe COVID-19, and therefore improve clinical outcomes [ 38 ].…”
Section: Place Of Baricitinib In the Management Of Moderate To Severe...mentioning
confidence: 99%
“…Recently, the combination therapy of Janus kinase (JAK) inhibitor baricitinib has been granted emergency use authorization for COVID-19 hospitalized patients [ 158 ]. Emanuelle Machado Marinho et.al in their study showed that baricitinib can interact powerfully with the Mpro.…”
Section: Discussionmentioning
confidence: 99%